2018
DOI: 10.1016/j.apsusc.2018.06.282
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of metal phthalocyanines with carbon zigzag and armchair nanotubes with different diameters

Abstract: Quantum-chemical calculations of the association of metal free, cobalt, copper and zinc phthalocyanines (MPc) with carbon zigzag and armchair nanotubes (CNTs) with diameters in the range of 7-14 Å were carried out by the DFT method with the use of BH van der Waals density functional and DZP atomic basis set. It was shown that interaction energy between the phthalocyanine molecules and the CNTs, as a whole, increases with an increase of the diameter of carbon nanotubes.However, in the case of CNT(n,0) the energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…In comparison with the combined state of BN180 and BN90, the former released more energy and was relatively stable. This was consistent with [55], which found that the interaction energy between the phthalocyanine molecules and the carbon nanotubes increased with an increase in the diameter of the CNTs. The reaction enthalpy between the four complexes and BN90/BN180 was ranked as follows: CePc 2 < EuPc 2 < TbPc 2 < YbPc 2 , coinciding with the order of their atomic numbers.…”
Section: Reaction Enthalpy Bond Length and Bond Anglesupporting
confidence: 90%
“…In comparison with the combined state of BN180 and BN90, the former released more energy and was relatively stable. This was consistent with [55], which found that the interaction energy between the phthalocyanine molecules and the carbon nanotubes increased with an increase in the diameter of the CNTs. The reaction enthalpy between the four complexes and BN90/BN180 was ranked as follows: CePc 2 < EuPc 2 < TbPc 2 < YbPc 2 , coinciding with the order of their atomic numbers.…”
Section: Reaction Enthalpy Bond Length and Bond Anglesupporting
confidence: 90%
“…In addition to the difference in the ammonium structure, the main difference in the chemical structure between the PAMAM salts and PVBC-TMA is that PVBC-TMA contains a large amount of benzene rings while PAMAM does not. π–π interaction between aromatic rings also is a widely existing nonbonding weak interaction. , Here, the cavity structure containing benzene rings of the hyperbranched PVBC-TMA was thought to be able to easily interact with the benzene due to the π–π interaction formed between the benzene ring in PVBC-TMA with the benzene in the solution. Hence, this afforded PVBC-TMA the higher extraction performance than the PAMAM salts having no benzene rings, although the binding of benzene with the quaternary ammonium in PVBC-TMA is weaker than with −CH 2 NH 3 + in PAMAM salts.…”
Section: Results and Discussionmentioning
confidence: 99%